Fe3O4-coated FeMgAl-LDH magnetic catalyst, preparation method thereof and application of Fe3O4-coated FeMgAl-LDH magnetic catalyst in catalysis of condensation reaction of furfural and acetone
The fe3O4@FeMgAl-LDH magnetic catalyst is wrapped with Fe3O4 and FeMgAl-LDH, and the selection and recovery problems of existing catalysts in the catalytic condensation reaction between furfural and acetone are solved, achieving efficient and economical catalytic effects and easy recovery of catalysts.
Patent Information
- Application Number
- CN202411652972.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing catalysts have selectivity and recycling problems in the catalytic condensation reaction of furfural and acetone, and the CaO fixation method is prone to fall off, resulting in high costs and equipment corrosion.
Fe3O4@FeMgAl-LDH magnetic catalyst was used, which was prepared by co-precipitation reaction. FeMgAl-LDH was encapsulated on the Fe3O4 surface and had a magnetic and layered structure, which simplified the recovery and separation of the catalyst.
The 100% conversion rate of furfural and 99.8% yield of furfural and difuryl acetone were achieved. The activity remained above 90% after the catalyst was reused for 5 times, which significantly reduced the raw material cost of the catalyst.
Smart Images

Figure CN119549148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of green catalysis and biomass resource application, and relates to a Fe3O4@FeMgAl-LDH magnetic catalyst and a preparation method thereof, and application of the catalyst in catalyzing the condensation reaction of furfural and acetone. Background Art
[0002] Energy has always been a hot topic in global development. With the development of the times, non-renewable resources are gradually decreasing, and the search for new energy plays a vital role in the future development of science and technology. The use of fossil fuels leads to the production of a large amount of greenhouse gases and harmful gases. It is generally believed that the research of new energy such as bioenergy is the trend of the times.
[0003] Biomass, which is rich in sources and has large reserves, is the only renewable organic carbon resource. Efficient conversion and utilization of biomass can alleviate dependence on fossil resources. Straw is an important biomass resource with high economic utilization value. However, most straws are not well treated, and some are even directly burned, producing greenhouse gases such as carbon dioxide and methane. Turning straw into fuel is a way to alleviate energy and environmental problems. By converting straw into biomass raw materials, many high-value-added industrial chemicals such as furfural, levulinic acid, and 5-hydroxymethylfurfural can be prepared. As one of the platform compounds for biorefining, biomass furfural can be prepared from raw materials rich in hemicellulose and cellulose (agricultural and forestry wastes such as corn cobs, sugarcane bagasse, and wheat straw) through catalytic conversion. Furfural is a bridge between biomass raw materials and biorefining, which has attracted widespread attention from academia and industry. Catalysts are the key factor in solving the resource utilization of furfural. Although the catalytic performance of homogeneous catalysts is efficient, the cost of separating homogeneous catalysts from products is expensive, and long-term use is prone to corroding equipment. The research and development of heterogeneous catalysts is of great significance for catalyst recovery and cost saving.
[0004] Patent CN115611831A prepared a magnesium aluminum composite oxide (MgAl-LDO) catalyst, which was used to catalyze the condensation reaction of furfural and acetone. The reaction was carried out at a temperature of 120°C for 2 hours, and the conversion rate of furfural was 99%. Patent application CN109759046A prepared a CaO / magnesium aluminum hydrotalcite catalyst, which was used to catalyze the condensation reaction of furfural and acetone. Under the optimal conditions, the conversion rate of furfural was 99%, and the total yield of furfurylidene acetone and difurfurylidene acetone was 93.2%. The yield of the product and the recovery of the catalyst of the above catalyst need to be improved, and CaO is fixed on the magnesium aluminum hydrotalcite by loading, which is easy to fall off due to immersion or stirring. Therefore, in order to solve the selectivity and recovery problems of the catalyst, it is urgent to develop a more economical, green, efficient and easily recyclable catalyst. Summary of the invention
[0005] The purpose of the present invention is to provide a magnetic nano-layered metal hydroxide catalyst (Fe3O4@FeMgAl-LDH magnetic catalyst) to solve the above-mentioned problems in the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A Fe3O4@FeMgAl-LDH magnetic catalyst comprises FeMgAl-LDH (ferromagnesium aluminum hydrotalcite) and Fe3O4.
[0008] The Fe3O4@FeMgAl-LDH magnetic catalyst is prepared by wrapping FeMgAl-LDH on the surface of Fe3O4.
[0009] The FeMgAl-LDH is prepared by coprecipitation reaction using solution A and solution B as raw materials.
[0010] The Fe3O4@FeMgAl-LDH magnetic catalyst is prepared by the following method, comprising: simultaneously dropping solution A and solution B into Fe3O4 aqueous dispersion for coprecipitation reaction, followed by aging, and the obtained precipitate is Fe3O4@FeMgAl-LDH magnetic catalyst; wherein the solution A is Fe 3+ 、Al 3+ and Mg 2+ A mixed aqueous solution, wherein solution B is OH - and CO3 2- of a mixed aqueous solution.
[0011] Preferably, the solution A is Fe 3+ A nitrate, hydrochloride or sulfate of Mg 2+ A nitrate, hydrochloride or sulfate of Al 3+ A mixed aqueous solution of a nitrate, hydrochloride or sulfate.
[0012] Preferably, the Fe3O4 aqueous dispersion is prepared by mixing Fe3O4 and water in a dosage ratio of 0.2:20 to 1:20 g / mL.
[0013] The Fe3O4, Fe 3+ 、Al 3+ and Mg 2+ The ratio of the total amount of substance to the amount of substance of Fe3O4 is 100:2.5 to 100:11.2.
[0014] Preferably, the Fe3O4, Fe 3+ 、Al 3+ and Mg 2+The ratio of the total amount of substance to the amount of substance of Fe3O4 is 100:4.5 to 100:5.6.
[0015] Most preferably, the Fe3O4, Fe 3+ 、Al 3+ and Mg 2+ The ratio of the total amount of substance to the amount of substance of Fe3O4 is 100:5.5~100:5.6.
[0016] The Fe 3+ Mg 2+ 、Al 3+ The molar ratio of the substances is (0.1~0.4):2:1.
[0017] Preferably, the Fe 3+ Mg 2+ 、Al 3+ The molar ratio of the substances is (0.3~0.4):2:1.
[0018] Most preferably, the Fe 3+ Mg 2+ 、Al 3+ The molar ratio of substances is 0.4:2:1.
[0019] Preferably, the solution B is a mixed aqueous solution of NaOH and Na2CO3.
[0020] The OH - and CO3 2- The amount of substances satisfy:
[0021]
[0022] in, Mg 2+ The amount of substance; For Al 3+ and Fe 3+ The total amount of substance.
[0023] Preferably, the OH - and CO3 2- The amount of substances satisfy:
[0024]
[0025] The Fe 3+ It is made of Fe 3+ One of the nitrates, hydrochlorides or sulfates provided, Mg 2+ It is composed of Mg 2+ A nitrate, hydrochloride or sulfate of Al 3+By Al 3+ One of the nitrate, hydrochloride or sulfate salts is provided.
[0026] The second object of the present invention is to provide a method for preparing the Fe3O4@FeMgAl-LDH magnetic catalyst, comprising: heating the Fe3O4 aqueous dispersion solution to the coprecipitation reaction temperature, adding solution A and solution B simultaneously under stirring conditions, and always keeping the pH of the mixed solution at 9 to 10 during the dropping process. After the dropping is completed, aging under stirring, and the obtained precipitate is the Fe3O4@FeMgAl-LDH magnetic catalyst.
[0027] The coprecipitation reaction temperature is 55-65°C, preferably 60°C.
[0028] The pH of the coprecipitation reaction is controlled at 9-10.
[0029] The aging temperature is 55-65°C, preferably 60°C.
[0030] The aging time is 6 to 10 hours, preferably 12 hours.
[0031] As a further preferred technical solution of the preparation method of the Fe3O4@FeMgAl-LDH magnetic catalyst of the present invention, it also includes: after aging, filtering is performed, and the filter cake is washed, filtered, dried and ground in sequence.
[0032] Preferably, the washing is to use deionized water to wash the filter cake until the pH of the filtrate is 7.
[0033] Preferably, the drying temperature is 80-110° C., the drying time is 12-24 hours, and the drying equipment is a drying box or an oven.
[0034] The third object of the present invention is to provide the application of the Fe3O4@FeMgAl-LDH magnetic catalyst in catalyzing the condensation reaction of furfural and acetone.
[0035] A method for preparing furfurylideneacetone (FAc) and difurfurylideneacetone (F2Ac) through a condensation reaction of furfural and acetone, comprising: using a Fe3O4@FeMgAl-LDH magnetic catalyst to catalyze a condensation reaction of furfural and acetone to generate furfurylideneacetone (FAc) and difurfurylideneacetone (F2Ac).
[0036] The molar ratio of furfural to acetone is 1:2 to 1:12, preferably 1:8 to 1:10, and most preferably 1:10.
[0037] The added amount of the Fe3O4@FeMgAl-LDH catalyst is 1-10wt% of the total amount of furfural and acetone, preferably 5wt%.
[0038] The condensation reaction time is 1 to 140 minutes, preferably 120 minutes.
[0039] The temperature of the condensation reaction is 80-160°C, preferably 160°C.
[0040] Catalytic mechanism:
[0041] The mechanism of the condensation reaction of furfural and acetone is shown in the figure Figure 1 As shown in the figure, the multi-hydroxy structure of Fe3O4@FeMgAl-LDH provides a large number of basic sites for catalysis. 3+ After the hydroxide is formed, a trace amount of oxide will be formed during the aging process, providing certain acidic sites. The entire catalytic process is dominated by alkalinity and supplemented by acidity. Under the action of alkali, the α-carbon of acetone loses protons to form carbon anions, which enhances its nucleophilicity. Under the action of acidic sites, the carbonyl oxygen atom of the furfural molecule is protonated, which enhances the electrophilicity of the carbonyl carbon and promotes the formation of furfurylideneacetone (FAc). Then, FAc is dehydrated under the dominance of alkalinity to form difurfurylideneacetone (F2Ac).
[0042] The beneficial effects of the present invention are:
[0043] (1) The Fe3O4@FeMgAl-LDH magnetic catalyst of the present invention is a magnetic nano-hydrotalcite, which has a layered structure and a large specific surface area.
[0044] (2) The magnetic core of the Fe3O4@FeMgAl-LDH magnetic catalyst of the present invention is Fe3O4. 3+ Mg 2+ 、Al 3+ Combined with the constructed hydrotalcite, the magnetic core Fe3O4 is directly wrapped in the hydrotalcite, and the layer structure of the hydrotalcite will not be destroyed due to the combination with the magnetic core, avoiding the problem of the magnetic core Fe3O4 directly loaded on the hydrotalcite easily falling off due to stirring, which is beneficial to the recovery of the catalyst.
[0045] (3) The preparation process of the Fe3O4@FeMgAl-LDH magnetic catalyst of the present invention is simple and inexpensive, and has high economic benefits.
[0046] (4) The addition of magnetic Fe3O4 makes the Fe3O4@FeMgAl-LDH magnetic catalyst of the present invention magnetic. After catalyzing the condensation reaction of furfural and acetone, the catalyst can be separated by magnetic attraction and is easy to recover, which simplifies the steps of separating the product and the catalyst and greatly saves the raw material cost of the catalyst. It has certain industrial practical value.
[0047] (5) The addition of magnetic Fe3O4 increases the specific surface area of the catalyst, improves the dispersibility and catalytic activity of the catalyst, allows more acetone to be adsorbed on the catalyst, increases the probability of carbon anions contacting furfural, and further increases the raw material conversion rate and product selectivity. The Fe3O4@FeMgAl-LDH magnetic catalyst of the present invention is used to catalyze the condensation reaction of furfural and acetone. Under the optimal conditions, the conversion rate of furfural is 100%, the total yield of the monocondensation product FAc (furfurylideneacetone) and the dicondensation product F2Ac (difurfurylideneacetone) is above 99.8%, and the catalytic activity does not change significantly after the catalyst is reused 5 times, and the product yield can still be maintained above 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is the mechanism diagram of the condensation of furfural and acetone catalyzed by Fe3O4@FeMgAl-LDH magnetic catalyst.
[0049] Figure 2 ] are SEM images of FeMgAl-LDH and Fe3O4@FeMgAl-LDH catalysts (Example 1); wherein a is the SEM image of FeMgAl-LDH, and b is the SEM image of Fe3O4@FeMgAl-LDH catalyst.
[0050] Figure 3 XRD patterns of Fe3O4@FeMgAl-LDH catalysts with different Fe contents.
[0051] Figure 4 FT-IR graphs of Fe3O4@FeMgAl-LDH catalysts with different Fe contents.
[0052] Figure 5 The adsorption-desorption curves of Fe3O4@FeMgAl-LDH catalysts with different Fe contents. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is described in more detail below in conjunction with embodiments, but these embodiments do not limit the protection scope of the present invention.
[0054] Example 1
[0055] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.4:2:1, 1.62g Fe(NO3)3·9H2O (0.004mol), 5.13g Mg(NO3)2·6H2O (0.02mol) and 3.75g Al(NO3)3·9H2O (0.01mol) were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0056] According to the formula Calculate the amount of NaOH and Na2CO3 respectively, take 2.176g NaOH and 2.97g Na2CO3 and dissolve them in 100mL deionized water to prepare a mixed alkaline aqueous solution, recorded as solution B.
[0057] In a four-necked flask, add about 20 mL of deionized water in advance, add 0.5 g of Fe3O4 (0.002 mol), disperse evenly, and obtain a Fe3O4 aqueous dispersion. The Fe3O4 aqueous dispersion is heated to 60°C, and solution A and solution B are simultaneously added dropwise to the four-necked flask under stirring. The pH value of the mixed solution is always maintained at 9-10 during the dropping process. After the dropping is completed, stirring and aging are continued at a temperature of 60°C for 12 hours. After the aging is completed, the mixed solution is filtered, and the filter cake is washed with deionized water until the filtrate is neutral. It is dried in an oven at 105°C for 24 hours to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 5.5% Fe3O4@FeMgAl, and ground into powder for standby use.
[0058] According to the preparation method of Fe3O4@FeMgAl-LDH magnetic catalyst in this embodiment, the difference is that the Fe3O4 aqueous dispersion is replaced with an equal volume of deionized water, and the iron magnesium aluminum hydrotalcite FeMgAl-LDH is prepared by coprecipitation method, which is recorded as FeMgAl-0.4:2:1 (Comparative Example 4). Figure 2 a. From Figure 2 It can be seen that FeMgAl-LDH presents a typical hydrotalcite-like layered structure, which is composed of metal oxide sheets. The sheets are connected by excess positive charges generated by anion neutralization. Its grains are hexagonal and the grain size is less than 500nm, indicating that the co-precipitation method can prepare nano-sized hydrotalcite. The SEM image of the prepared 5.5% Fe3O4@FeMgAl is shown in Figure 1. Figure 2 As shown in b. Figure 2 b It can be seen that the nano-FeMgAl-LDH shell is wrapped on the surface of the Fe3O4 magnetic core and forms a spherical structure, but the morphology of the FeMgAl-LDH on the surface is similar, and the shell still presents a hexagonal flake structure.
[0059] The XRD pattern of the prepared 5.5% Fe3O4@FeMgAl is shown in Figure 3 As shown. Figure 3 It can be seen that the strong peaks at the lower diffraction angles of 11.5°, 24° and 35° are attributed to the diffraction from the d003, d006 and d102 basal planes, and the lower intensity peaks appearing at the higher diffraction angles of 39°, 46°, 61° and 62° are assigned to the diffraction from the d105, d108, d110 and d113 basal planes. These patterns clearly show the crystal structure of hydrotalcite, which also shows that the present invention successfully synthesized Fe3O4 / FeMgAl-LDH.
[0060] The FT-IR image of the prepared 5.5% Fe3O4@FeMgAl is shown in Figure 4 As shown in the figure, 5.5%Fe3O4@FeMgAl has a -1 There is a strong and broad absorption band near 1650cm, which is the hydrogen bonding and OH stretching vibration peak of water molecules on the surface and between the octahedral layers. -1 Another absorption band corresponding to water deformation was found at 1358 and 1380 cm -1 CO3 appears around 2- Asymmetric vibration peaks, half of the interlayer carbonate ions are replaced by hydroxyl ions. 400-900cm -1 The vibration peaks are the stretching vibration and bending vibration of MO and M-OH (M = Mg, Al), 560 cm -1 All these indicate that hydrotalcite is successfully synthesized.
[0061] The N2 adsorption-desorption curve of the prepared 5.5% Fe3O4@FeMgAl is shown in Figure 5 As shown in the figure, its N2 adsorption-desorption curve belongs to the H3 type isotherm, indicating that 5.5%Fe3O4@FeMgAl is a typical mesoporous material. The specific surface area (S BET ), pore volume and pore size are shown in Table 1. Its specific surface area reaches 152.64m 2 / g.
[0062] Catalyst performance evaluation: 0.89g of 5.5% Fe3O4@FeMgAl catalyst was loaded into a 50mL reactor, and 2.3g of furfural and 15.6g of acetone were added. The reactor was sealed and heated. When heated to 160°C, the reaction was stirred for 120 minutes. After the reaction, samples were taken and tested by gas chromatography. The conversion rate of furfural was 100%, the total selectivity of the product was 99.8%, and the yield was 99.8%. In order to evaluate the repeatability of the catalyst, after each experiment, the catalyst was recovered with a magnet, washed with ethanol, and dried in a vacuum drying oven for the next reaction. The catalyst was reused 5 times, and the conversion rate of furfural remained at about 99.1%, the activity of the catalyst did not decrease significantly, and the product yield remained at 96.6%; after being reused 5 times, the XRD pattern of 5.5% Fe3O4@FeMgAl was as follows Figure 3 As shown in the FT-IR diagram Figure 4As shown, there is no obvious change in the catalyst structure after being reused for 5 times, which shows that the present invention directly wraps the magnetic core Fe3O4 in the hydrotalcite, avoiding the problem that the magnetic core Fe3O4 is easily detached due to stirring when it is directly loaded on the hydrotalcite, which is beneficial to the recovery of the catalyst.
[0063] Example 2
[0064] The preparation of 6.1% Fe3O4@FeMgAl is the same as that of Example 1, except that the molar ratio of the metal elements Fe, Mg and Al is 0.1:2:1.
[0065] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.1:2:1, 0.40g Fe(NO3)3·9H2O, 5.13g Mg(NO3)2·6H2O and 3.75g Al(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0066] According to the formula Calculate the amount of NaOH and Na2CO3 respectively, take 1.99g NaOH and 2.33g Na2CO3 and dissolve them in 100mL deionized water to prepare a mixed alkaline aqueous solution, recorded as solution B.
[0067] About 20 mL of deionized water was added to a four-necked flask in advance, and 0.5 g of Fe3O4 was added and dispersed evenly to obtain a Fe3O4 aqueous dispersion. The Fe3O4 aqueous dispersion was heated to 60°C, and solution A and solution B were simultaneously added dropwise to the four-necked flask under stirring. The pH of the mixed solution was always maintained at 9-10 during the dropping process. After the dropping was completed, stirring was continued and the mixture was aged at 60°C for 12 h. After the aging was completed, the mixed solution was filtered, and the filter cake was washed with deionized water until the filtrate was neutral. The mixture was dried in an oven at 105°C for 24 h to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 6.1% Fe3O4@FeMgAl, and ground into powder for standby use.
[0068] The XRD pattern of the prepared 6.1% Fe3O4@FeMgAl is shown in Figure 3 As shown. Figure 3 It can be seen that the strong peaks at lower diffraction angles of 11.5°, 24° and 35° are attributed to the diffraction from the d003, d006 and d102 basal planes, and the lower intensity peaks appearing at higher diffraction angles of 39°, 46°, 61° and 62° are assigned to the diffraction from the d105, d108, d110 and d113 basal planes. These patterns clearly show the crystal structure of hydrotalcite, which also indicates the successful synthesis of Fe3O4 / FeMgAl-LDH.
[0069] The FT-IR image of the prepared 6.1% Fe3O4@FeMgAl is shown in Figure 4 As shown in the figure, 6.1%Fe3O4@FeMgAl has a -1 There is a strong and broad absorption band near 1650cm, which is the hydrogen bonding and OH stretching vibration peak of water molecules on the surface and between the octahedral layers. -1 Another absorption band corresponding to water deformation was found at 1358 and 1380 cm -1 CO3 appears around 2- Asymmetric vibration peaks, half of the interlayer carbonate ions are replaced by hydroxyl ions. 400-900cm -1 The vibration peaks are the stretching vibration and bending vibration of MO and M-OH (M = Mg, Al), 560 cm -1 All these indicate that hydrotalcite is successfully synthesized.
[0070] The N2 adsorption-desorption curve of the prepared 6.1% Fe3O4@FeMgAl is shown in Figure 5 As shown, its N2 adsorption-desorption curve belongs to the H3 type isotherm, indicating that 6.1%Fe3O4@FeMgAl is a typical mesoporous material. The specific surface area, pore volume and pore size of 6.1%Fe3O4@FeMgAl-LDH catalyst are shown in Table 1.
[0071] The performance evaluation of the catalyst was the same as that of Example 1, and the conversion rate of furfural was 84.9%, the total selectivity of the product was 98.8%, and the yield was 83.9%.
[0072] Example 3
[0073] The preparation of 5.9% Fe3O4@FeMgAl is the same as that in Example 1, except that the molar ratio of the metal elements Fe, Mg and Al is 0.2:2:1.
[0074] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.2:2:1, 0.81g Fe(NO3)3·9H2O, 5.13g Mg(NO3)2·6H2O and 3.75g Al(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0075] According to the formula Calculate the amount of NaOH and Na2CO3 respectively, take 2.05g NaOH and 2.54g Na2CO3 and dissolve them in 100mL deionized water to prepare a mixed alkaline aqueous solution, recorded as solution B.
[0076] Add about 20 mL of deionized water into a four-necked flask in advance, and add 0.5 g of Fe3O4 and disperse evenly to obtain a Fe3O4 aqueous dispersion. Heat the Fe3O4 aqueous dispersion to 60°C, and drop solutions A and B into the four-necked flask at the same time under stirring. Keep the pH of the mixed solution at 9-10 during the dropping process. Continue stirring after the dropping is completed. Age at 60°C for 12 hours. After the aging is completed, filter the mixed solution, wash the filter cake with deionized water until the filtrate is neutral, and then bake it in an oven at 105°C for 24 hours to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 5.9% Fe3O4@FeMgAl, and grind it into powder for standby use.
[0077] The XRD pattern of the prepared 5.9% Fe3O4@FeMgAl is shown in Figure 3 As shown. Figure 3 It can be seen that the strong peaks at lower diffraction angles of 11.5°, 24° and 35° are attributed to the diffraction from the d003, d006 and d102 basal planes, and the lower intensity peaks appearing at higher diffraction angles of 39°, 46°, 61° and 62° are assigned to the diffraction from the d105, d108, d110 and d113 basal planes. These patterns clearly show the crystal structure of hydrotalcite, which also indicates the successful synthesis of Fe3O4 / FeMgAl-LDH.
[0078] The FT-IR image of the prepared 5.9% Fe3O4@FeMgAl is shown in Figure 4 As shown in the figure, 5.9%Fe3O4@FeMgAl at 3439cm -1 There is a strong and broad absorption band near 1650cm, which is the hydrogen bonding and OH stretching vibration peak of water molecules on the surface and between the octahedral layers. -1 Another absorption band corresponding to water deformation was found at 1358 and 1380 cm -1 CO3 appears around 2- Asymmetric vibration peaks, half of the interlayer carbonate ions are replaced by hydroxyl ions. 400-900cm -1 The vibration peaks are the stretching vibration and bending vibration of MO and M-OH (M = Mg, Al), 560 cm -1 All these indicate that hydrotalcite is successfully synthesized.
[0079] The N2 adsorption-desorption curve of the prepared 5.9% Fe3O4@FeMgAl is shown in Figure 5As shown, its N2 adsorption-desorption curve belongs to the H3 type isotherm, indicating that 5.9%Fe3O4@FeMgAl is a typical mesoporous material. The specific surface area, pore volume and pore size of 5.9%Fe3O4@FeMgAl-LDH catalyst are shown in Table 1.
[0080] The performance evaluation of the catalyst was the same as in Example 1, and the furfural conversion rate was 89.2%, the total product selectivity was 99.3%, and the yield was 88.6%.
[0081] Example 4
[0082] The preparation of 5.7% Fe3O4@FeMgAl is the same as that of Example 1, except that the molar ratio of the metal elements Fe, Mg, and Al is 0.3:2:1.
[0083] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.3:2:1, 1.22g Fe(NO3)3·9H2O, 5.13g Mg(NO3)2·6H2O and 3.75g Al(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0084] According to the formula Calculate the amount of NaOH and Na2CO3 respectively, take 2.11g NaOH and 2.76g Na2CO3 and dissolve them in 100mL deionized water to prepare a mixed alkaline aqueous solution, recorded as solution B.
[0085] Add about 20 mL of deionized water into a four-necked flask in advance, and add 0.5 g of Fe3O4 and disperse evenly to obtain a Fe3O4 aqueous dispersion. Heat the Fe3O4 aqueous dispersion to 60°C, and drop solutions A and B into the four-necked flask at the same time under stirring. Keep the pH of the mixed solution at 9-10 during the dropping process. Continue stirring after the dropping is completed. Age at 60°C for 12 hours. After the aging is completed, filter the mixed solution, wash the filter cake with deionized water until the filtrate is neutral, and then bake it in an oven at 105°C for 24 hours to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 5.7% Fe3O4@FeMgAl, and grind it into powder for standby use.
[0086] The XRD pattern of the prepared 5.7% Fe3O4@FeMgAl is shown in Figure 3 As shown. Figure 3It can be seen that the strong peaks at lower diffraction angles of 11.5°, 24° and 35° are attributed to the diffraction from the d003, d006 and d102 basal planes, and the lower intensity peaks appearing at higher diffraction angles of 39°, 46°, 61° and 62° are assigned to the diffraction from the d105, d108, d110 and d113 basal planes. These patterns clearly show the crystal structure of hydrotalcite, which also indicates the successful synthesis of Fe3O4 / FeMgAl-LDH.
[0087] The FT-IR image of the prepared 5.7% Fe3O4@FeMgAl is shown in Figure 4 As shown in the figure, 5.7%Fe3O4@FeMgAl has a -1 There is a strong and broad absorption band near 1650cm, which is the hydrogen bonding and OH stretching vibration peak of water molecules on the surface and between the octahedral layers. -1 Another absorption band corresponding to water deformation was found at 1358 and 1380 cm -1 CO3 appears around 2- Asymmetric vibration peaks, half of the interlayer carbonate ions are replaced by hydroxyl ions. 400-900cm -1 The vibration peaks are the stretching vibration and bending vibration of MO and M-OH (M = Mg, Al), 560 cm -1 All these indicate that hydrotalcite is successfully synthesized.
[0088] The N2 adsorption-desorption curve of the prepared 5.7% Fe3O4@FeMgAl is shown in Figure 5 As shown, its N2 adsorption-desorption curve belongs to the H3 type isotherm, indicating that 5.7%Fe3O4@FeMgAl is a typical mesoporous material. The specific surface area, pore volume and pore size of 5.7%Fe3O4@FeMgAl-LDH catalyst are shown in Table 1.
[0089] The performance evaluation of the catalyst was the same as in Example 1, and the furfural conversion rate was 93.5%, the total product selectivity was 99.1%, and the yield was 92.7%.
[0090] Example 5
[0091] The preparation of 2.5% Fe3O4@FeMgAl is the same as that of Example 1, except that the addition amount of the magnetic core Fe3O4 is 0.2 g.
[0092] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.4:2:1, 1.62g Fe(NO3)3·9H2O, 5.13g Mg(NO3)2·6H2O and 3.75g Al(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0093] According to the formula Calculate the amount of NaOH and Na2CO3 respectively, take 2.18g NaOH and 2.97g Na2CO3 and dissolve them in 100mL deionized water to prepare a mixed alkaline aqueous solution, recorded as solution B.
[0094] In a four-necked flask, add about 20 mL of deionized water in advance, and add 0.2 g of Fe3O4 and disperse evenly to obtain a Fe3O4 aqueous dispersion. The Fe3O4 aqueous dispersion is heated to 60°C, and solution A and B are simultaneously added dropwise to the flask under stirring. The pH of the mixed solution is always maintained at 9-10 during the dropping process. After the dropping is completed, stirring is continued. The mixture is aged at 60°C for 12 hours. After the aging is completed, the mixed solution is filtered, and the filter cake is washed with deionized water until the filtrate is neutral. Then, it is dried in an oven at 105°C for 24 hours to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 2.5% Fe3O4@FeMgAl, and ground into powder for standby use.
[0095] The performance evaluation of the catalyst was the same as in Example 1, and the furfural conversion rate was 85.3%, the total product selectivity was 98.3%, and the yield was 83.9%.
[0096] Example 6
[0097] The preparation of 4.8% Fe3O4@FeMgAl is the same as that in Example 1, except that the amount of the magnetic core Fe3O4 added is 0.4 g.
[0098] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.4:2:1, 1.62g Fe(NO3)3·9H2O, 5.13g Mg(NO3)2·6H2O and 3.75g Al(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0099] The preparation of mixed alkaline solution B is the same as in Example 5.
[0100] In a four-necked flask, add about 20 mL of deionized water in advance, and add 0.4 g of Fe3O4 and disperse evenly to obtain a Fe3O4 aqueous dispersion. The Fe3O4 aqueous dispersion is heated to 60°C, and solution A and B are simultaneously added dropwise to the flask under stirring. The pH of the mixed solution is always maintained at 9-10 during the dropping process. After the dropping is completed, stirring is continued. The mixture is aged at 60°C for 12 hours. After the aging is completed, the mixed solution is filtered, and the filter cake is washed with deionized water until the filtrate is neutral, and then dried in an oven at 105°C for 24 hours to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 4.8% Fe3O4@FeMgAl, and ground into powder for standby use.
[0101] The performance evaluation of the catalyst was the same as in Example 1, and the furfural conversion rate was 96.5%, the total product selectivity was 96.7%, and the yield was 93.3%.
[0102] Example 7
[0103] The preparation of 9.1% Fe3O4@FeMgAl is the same as in Example 1, except that the amount of the added magnetic core Fe3O4 is 0.8 g.
[0104] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.4:2:1, 1.62g Fe(NO3)3·9H2O, 5.13g Mg(NO3)2·6H2O and 3.75g Al(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0105] The preparation of mixed alkaline solution B is the same as in Example 5.
[0106] About 20 mL of deionized water was added to a four-necked flask in advance, and 0.8 g of Fe3O4 was added and dispersed evenly to obtain a Fe3O4 aqueous dispersion. The Fe3O4 aqueous dispersion was heated to 60°C, and solutions A and B were simultaneously added dropwise to the flask under stirring conditions. The pH of the mixed solution was always maintained at 9-10 during the addition. After the addition was completed, stirring was continued and the mixture was aged at 60°C for 12 h. After the aging was completed, the mixed solution was filtered, and the filter cake was washed with deionized water until the filtrate was neutral, and then dried in an oven at 105°C for 24 h to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 9.1% Fe3O4@FeMgAl, and ground into powder for standby use.
[0107] The performance evaluation of the catalyst was the same as in Example 1, and the furfural conversion rate was 94.7%, the total product selectivity was 94.2%, and the yield was 89.2%.
[0108] Example 8
[0109] The preparation of 11.2% Fe3O4@FeMgAl is the same as that in Example 1, except that the amount of the added magnetic core Fe3O4 is 1 g.
[0110] According to the molar ratio of metal elements iron, magnesium and aluminum of 0.4:2:1, 1.62g Fe(NO3)3·9H2O, 5.13g Mg(NO3)2·6H2O and 3.75g Al(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0111] The preparation of mixed alkaline solution B is the same as in Example 5.
[0112] About 20 mL of deionized water was added to a four-necked flask in advance, and 1 g of Fe3O4 was added and dispersed evenly to obtain a Fe3O4 aqueous dispersion. The Fe3O4 aqueous dispersion was heated to 60°C, and solutions A and B were simultaneously added dropwise to the flask under stirring conditions. The pH of the mixed solution was always maintained at 9-10 during the addition. After the addition was completed, stirring was continued and the mixture was aged at 60°C for 12 h. After the aging was completed, the mixed solution was filtered, and the filter cake was washed with deionized water until the filtrate was neutral, and then dried to obtain a Fe3O4@FeMgAl-LDH magnetic catalyst, recorded as 11.2% Fe3O4@FeMgAl, and ground into powder for standby use.
[0113] The performance evaluation of the catalyst was the same as in Example 1, and the furfural conversion rate was 84.6%, the total product selectivity was 98.4%, and the yield was 83.2%.
[0114] Comparative Example 1
[0115] According to the molar ratio of metal elements magnesium and aluminum being 2:1, 5.13 g Mg(NO3)2·6H2O (0.02 mol) and 3.75 g Al(NO3)3·9H2O (0.01 mol) were weighed and dissolved in 100 mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0116] According to the formula Calculate the amount of NaOH and Na2CO3 respectively, take 1.92g NaOH and 2.12g Na2CO3 and dissolve them in 100mL deionized water to prepare a mixed alkaline aqueous solution, recorded as solution B.
[0117] About 20 mL of deionized water was added to a four-necked flask in advance, and solution A and solution B were simultaneously added dropwise to the four-necked flask under stirring. The pH value of the mixed solution was always maintained at 9-10 during the dropping process. After the dropping was completed, stirring and aging were continued at a temperature of 60°C for 12 hours. After the aging was completed, the mixed solution was filtered, and the filter cake was washed with deionized water until the filtrate was neutral. The filtrate was dried in an oven at 105°C for 24 hours to obtain the MgAl-LDH catalyst, which was ground into powder for standby use.
[0118] The catalyst performance evaluation was the same as in Example 1, except that the catalyst was MgAl-LDH. The conversion rate of furfural was 22.6%, the total product selectivity was 97.9%, and the yield was 22.1%.
[0119] Comparative Example 2
[0120] The MgAl-LDH prepared in Comparative Example 1 was placed in a muffle furnace and calcined at 450° C. for 3 h to prepare MgAl-LDO.
[0121] The catalyst performance evaluation was the same as that of Comparative Example 1, except that the catalyst was MgAl-LDO. The conversion rate of furfural was 45.0%, the total product selectivity was 91.1%, and the yield was 41.0%.
[0122] Comparative Example 3
[0123] According to the molar ratio of metal elements calcium, magnesium and aluminum of 1:2:1, 2.36g Ca(NO3)2·4H2O (0.01mol), 5.13g Mg(NO3)2·6H2O (0.02mol) and 3.75g Al(NO3)3·9H2O (0.01mol) were weighed and dissolved in 100mL deionized water to prepare a mixed salt water solution, which was recorded as solution A.
[0124] According to the formula Calculate the amount of NaOH and Na2CO3 respectively, take 2.56g NaOH and 2.12g Na2CO3 and dissolve them in 100mL deionized water to prepare a mixed alkaline aqueous solution, recorded as solution B.
[0125] About 20 mL of deionized water was added to a four-necked flask in advance, and solution A and solution B were simultaneously added dropwise to the four-necked flask under stirring. The pH value of the mixed solution was always maintained at 9-10 during the dropping process. After the dropping was completed, stirring and aging were continued at a temperature of 60°C for 12 hours. After the aging was completed, the mixed solution was filtered, and the filter cake was washed with deionized water until the filtrate was neutral. The filtrate was dried in an oven at 105°C for 24 hours to obtain the CaMgAl-LDH catalyst, which was ground into powder for standby use.
[0126] The catalyst performance evaluation was the same as in Example 1, except that the catalyst was CaMgAl-LDH. The conversion rate of furfural was 44.2%, the total product selectivity was 95.1%, and the yield was 42.0%.
[0127] Comparative Example 4
[0128] FeMgAl-LDH (denoted as FeMgAl-0.4:2:1) was prepared in the same manner as in Example 1, except that the Fe3O4 aqueous dispersion was replaced with an equal volume of deionized water. The SEM image of the prepared FeMgAl-LDH is shown in FIG. Figure 2 Its specific surface area, pore volume and pore diameter are shown in Table 1.
[0129] The catalyst performance evaluation was the same as in Example 1, except that the catalyst was FeMgAl-LDH. The conversion rate of furfural was 81.2%, the total product selectivity was 97.1%, and the yield was 78.8%.
[0130] Table 1. Specific surface area and pore volume and pore size of materials
[0131]
Claims
1. A Fe3O4@FeMgAl-LDH magnetic catalyst, characterized in that: The magnetic catalyst comprises FeMgAl-LDH and Fe3O4; the FeMgAl-LDH is prepared by coprecipitation reaction using solution A and solution B as raw materials; the solution A is Fe 3+ 、Al 3+ and Mg 2+ A mixed aqueous solution, wherein solution B is OH - and CO3 2- of a mixed aqueous solution.
2. The Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 1, characterized in that: The Fe3O4@FeMgAl-LDH magnetic catalyst is prepared by the following method: solution A and solution B are simultaneously added dropwise to a Fe3O4 aqueous dispersion for a coprecipitation reaction, followed by aging, and the obtained precipitate is the Fe3O4@FeMgAl-LDH magnetic catalyst.
3. The Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 1 or 2, characterized in that: The solution A is Fe 3+ A nitrate, hydrochloride or sulfate of Mg 2+ A nitrate, hydrochloride or sulfate of Al 3+ The solution B is a mixed aqueous solution of a nitrate, a hydrochloride or a sulfate; the solution B is a mixed aqueous solution of NaOH and Na2CO3.
4. The Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 1 or 2, characterized in that: The Fe3O4, Fe 3+ 、Al 3+ and Mg 2+ The ratio of the total amount of substance of Fe3O4 to the amount of substance of Fe3O4 is 100:2.5 to 100:11.2, preferably 100:4.5 to 100:5.6, more preferably 100:5.5 to 100:5.6; the Fe 3+ Mg 2+ 、Al 3+ The molar ratio of the substance is (0.1-0.4):2:1, preferably (0.3-0.4):2:1, more preferably 0.4:2:1; the OH - and CO3 2- The amount of substances satisfies: in, Mg 2+ The amount of substance; For Al 3+ and Fe 3+ The total amount of substance.
5. A method for preparing the Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 1, characterized in that: include: The Fe3O4 aqueous dispersion solution is heated to the coprecipitation reaction temperature, and solution A and solution B are added dropwise at the same time under stirring conditions. The pH value of the mixed solution is always kept at 9-10 during the dropping process. After the dropping is completed, the mixture is aged under stirring. After the aging is completed, the obtained precipitate is the Fe3O4@FeMgAl-LDH magnetic catalyst.
6. The method for preparing the Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 5, characterized in that: The coprecipitation reaction temperature is 55-65°C, preferably 60°C; the aging temperature is 55-65°C, preferably 60°C; the aging time is 6-10h, preferably 12h.
7. The method for preparing the Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 5, characterized in that: Also includes: After aging, the product is filtered and the filter cake is washed, filtered, dried and ground in sequence.
8. The method for preparing the Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 7, characterized in that: The washing is to use deionized water to wash the filter cake until the pH value of the filtrate is 7; the drying temperature is 80-110° C., and the drying time is 12-24 hours.
9. Use of the Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 1 in catalyzing the condensation reaction of furfural and acetone.
10. A method for preparing furfurylideneacetone and difurfurylideneacetone by condensation reaction of furfural and acetone, characterized in that: include: Using the Fe3O4@FeMgAl-LDH magnetic catalyst according to claim 1 to catalyze the condensation reaction of furfural and acetone to generate furfurylideneacetone and difurfurylideneacetone; Wherein, the molar ratio of furfural to acetone is 1:2 to 1:12, preferably 1:8 to 1:10, and most preferably 1:10; The Fe3O4@FeMgAl-LDH catalyst is added in an amount of 1-10wt% of the total amount of furfural and acetone, preferably 5wt%; The condensation reaction time is 1 to 140 minutes, preferably 120 minutes; The temperature of the condensation reaction is 80-160°C, preferably 160°C.
Citation Information
Patent Citations
Magnetic nano solid alkaline catalyst and method for synthesizing pseudoionone in presence of magnetic nano solid alkaline catalyst
CN102179250A
SnO2 / MgAl-LDO solid base and preparation method and application thereof
CN109433184A
Copper-chromium hydrotalcite catalyst as well as preparation method and application thereof
CN109876839A
Preparation method of g-C3N4 modified hydrotalcite catalyst and application of g-C3N4 modified hydrotalcite catalyst in furfural and cyclic ketone condensation reaction
CN114984991A
Production of lactones and production of esters
JP1995267899A
Cited By
Catalyst for preparing aviation fuel intermediate by catalyzing condensation reaction of furfural and acetone as well as preparation method and application of catalyst
CN120479476A